SINOPSIS DEL GÉNERO XANTHOPYGUS KRAATZ; 1857 (COLEOPTERA: STAPHYLINIDAE) DE MÉXICO - Navarrete Heredia, José Luis (Instituto de Ecología, A.C., 2004)
A synopsis of the genus Xanthopygus Kraatz, 1857 (Coleoptera: Staphylinidae) from Mexico is provided. In Mexico eight species are recorded. A key for Mexican species, taxonomic notes and specific data on distributions and habits are also included. Lectotypes (L) and paralectotypes (PL) are designated for X. flohri Sharp, 1884 (L) and X. morosus Sharp, 1884 (L, PL).